Pengaruh Harga, Kualitas Produk dan Citra Merek Terhadap Keputusan Pembelian Smartphone Xiaomi (Studi Kasus Mahasiswa Fakultas Ekonomi Universitas Hasyim Asy’ari) - Nur Hadi (BIMA : Journal of Business and Innovation Management, 2019)
This study aims to find out the Effect of Price, Product Quality and Brand Image on Purchasing Decisions of Xiaomi Smartphones (a case study of the Faculty of Economics, Hasyim Asy'ari University). This study uses quantitative data analysis techniques with survey data collection techniques (observation) using primary data obtained from the questionnaire. The sample in this study was 50 respondents. Samples were taken with a saturated sampling technique where all populations were sampled in the study. Data analysis techniques using Multiple Linear Regression. The results showed that: (1) price had a significant effect on purchasing decisions. (2) product quality has a significant effect on purchasing decisions (3) brand image has a significant effect on purchasing decisions (4) price, product quality and brand image have a significant (simultaneous) influence on purchasing decisions of Xiaomi smartphones.